Solution to n-Queens Problem: Heuristic Approach - Osaghae, Edgar (Transactions on Engineering and Computing Sciences, 2021)
Finding non-backtracking solutions to n-queens problems, has been very challenging. Several researchers have attempting to find non-backtracking solutions to n-queens problem, although, some of them recorded huge successes in their researches, but none of them have attempting using the implications of even and odd n-queens, to find solutions to the n-queens problem. In this paper, an attempt was made to extract patterns created from even-numbered n-queens and odd-numbered n-queens placements on the chessboard. The research started from experimenting the placements of non-attacking queens for 4-queens, 16-queens, 32-queens and n-queens. After the experimenting with the placements of different number of queens on the chessboard, it was revealed that even-numbered and odd-numbered queens, have pattern of placement of queens. The results of this research work show how to start and finish placements of queens on the chessboard, depending on whether the n number of queens are either even or odd, using heuristic approach.